Investigation of biological activities of Mallotus paniculatus leaf extract - Nur Aliah Bahaman (Kulliyyah of Engineering, International Islamic University Malaysia, 2020)
In this study, Mallotus paniculatus (Balik Angin), a plant that was easily found in both rural and urban areas was screened against several biological activities. Traditionally, M. paniculatus is used in curing various diseases such as a remedy after child's birth, wound healing and fever treatment. In the present study, four biological properties of the plant were screened, which include antibacterial, antifungal, anticancer and antioxidant activities. Today, synthetic drugs are extensively used in curing most of the human diseases. However, they are expensive, difficult to access for remote areas as well as have limited application for specific treatment compared to the natural products from plants which may be effective against several diseases. Hence, for screening purpose, potential biological compounds were extracted from the plant leaves by sonication with different type of solvents namely hexane, ethyl acetate, and ethanol. The extracted compounds were tested for antibacterial and antifungal properties using disc diffusion agar and broth dilution assay, antioxidant using DPPH scavenging assay and anticancer using MTT assay. From the screening results, M. paniculatus ethanolic extract was shown to possess antibacterial, antioxidant and anticancer but not antifungal property. While, ethyl acetate and hexane extracts showed weak or no contribution to any of these activities. The ethanolic extract was also shown to have outstanding antioxidant activity (IC50 30 μg/ml) that is comparable with positive control, butylated hydroxytoluene (BHT) (IC50 30 μg/ml) compared to other biological properties. Due to this, the present study focused on optimizing the sonication extraction process condition for extract with antioxidant activity. Using Face Centered Central Design (FCCCD) to design optimization experiments, the data obtained from the experiments were fit to polynomial equation to determine the best extraction condition. The optimum condition obtain from this study was at 30ºC for 30 min where it gave IC50 value of antioxidant activity, 27 μg/ml. Partial purification was carried out to identify which types of compound responsible for the antioxidant activity in the ethanolic extract by fractionation (partitioning) method followed by TLC analysis. It was observed that the extract from partitioning possibly consist of polar compounds which may be responsible for the antioxidant property. In conclusion, M. paniculatus possesses multiple medical properties in which its antioxidant property is worth to be further investigated using optimized extraction condition determined in this study.